ECONOMIC VALUE OF CRITICAL LAND IN SEMPAYANG VILLAGE, NORTH KALIMANTAN - Sulistya Rini Pratiwi; Yohanna Thresia Nainggolan; Meylin Rahmawati (MESP–FEB UNS, 2023)
Land resources play an important role in supporting agricultural development. Land is a habitat of the growth of various kinds of vegetation as the provider for various food sources, so it is very important to do conservation for some critical land. Therefore some disasters such as floods, erosion and drought can be suppressed. One of negative impacts of the critical land disaster is a productivity decrease in farm. This study aims to identify the location of vulnerable areas of critical land and to examine the economic value of mitigation of vulnerable agricultural land in critical lands. Based on the results of the GIS analysis, the largest critical land area is in Malinau District. Almost all regions in Malinau Regency are vulnerable area of the critical land. The majority of respondents could pay between 26,000 - 30,000 IDR, which is 33.3%. Consumer surplus value is 2,520,000 IDR per person per year where farmers can produce 1-2 times a month or approximately 18 times a year. While the total economic value of farmers whose land is not critical land is 45,360,000 IDR.Keywords: Mitigation, dry land agriculture, contingent valuation method, agroeconomiec, border area.